The Effectiveness of Islamic Character Education in Enhancing Students’ Leadership, Discipline, and Moral Values - Mukhlis Mukhlis; Husna Husna; Ahyar Rasyidi; Uria Hasnan; Muhammad Yusuf; Ahmad Nordian (Al-Mukhlashin: Jurnal Multidisiplin Ilmu, 2026)
This study examines the effectiveness of Islamic character education in enhancing leadership, discipline, and moral development among students. The primary objective of this research is to analyze how Islamic character education contributes to shaping students’ leadership qualities, strengthening disciplinary behavior, and fostering moral integrity in educational institutions. The study employs a library research method by systematically reviewing books, peer-reviewed journal articles, and relevant academic publications related to Islamic education, character development, and student leadership. Data were analyzed through content analysis to identify recurring themes, conceptual frameworks, and empirical findings from previous studies. The results indicate that Islamic character education plays a significant role in developing leadership through value-based role modeling, strengthening discipline through habituation and moral supervision, and enhancing moral behavior through internalization of Islamic ethical principles. Furthermore, Islamic character education is shown to integrate spiritual, cognitive, and behavioral dimensions in a holistic manner. These findings suggest that Islamic character education is an effective approach to addressing moral decline and leadership challenges in contemporary education. The study concludes that the systematic implementation of Islamic character education can significantly contribute to the formation of disciplined, morally upright, and responsible future leaders.